Movelaria e fabricação digital: ressignificando a marcenaria tradicional com ênfase na inovação sustentável em design - Carvalho, Anamaria Ribeiro de Lima (2023)
Currently, the growing demand for digital technologies points to the need for new paths to traditional production practices. Under the assumption that there is still a lack of technical knowledge in the furniture sector regarding the use of digital manufacturing techniques applied to the production of solid wood furniture, research is focused on the possibility of integrating the two systems, traditional and digital, in the manufacture of furniture using solid wood. The object of study of this research are the practices and processes used in the manufacture of wooden furniture involving traditional techniques and digital technologies. Aspects of innovation and sustainability are also contemplated, understanding that they could not be disjointed from the context of this research, because they are relevant themes to the processes of development of productions nowadays. The main objective of the research is to contribute to the training of new professionals through the paradigm shift that allows the integration of traditional joinery techniques into the digital manufacturing system valuing the culture of sustainability and promoting innovation. The research of applied nature and qualitative approach seeks to generate knowledge for a practical application, investigating how such practices occur in the work of designers who effectively create, produce and commercialize solid wood furniture and the design contribution in relation to sustainability and innovation. Three spaces of shared joinery were also analyzed, to better understand the integration of traditional techniques combined with digital Technologies in the context of small-scale production. The methods used were literature review, survey and case study. Due to the pandemic context (COVID-19) experienced during the development of the dissertation, the survey method and case studies were conducted in a virtual environment following the protocols of the Research Ethics Committee of the Brazil Platform. The results indicate that there already are initiatives to approximate the artisanal techniques of joinery with the digital manufacturing system using solid wood, but investigations are necessary to identify the tools capable of supporting this integration, preserving the essence of artisanal work, and crossing the barriers that prevent access and knowledge of available technologies.